Does Where You Live Matter? An Analysis of Intergenerational Transmission of Education Among Hispanic Americans - Wang, Sharron Xuanren; Sakamoto, Arthur (Frontiers in Sociology, 2021)
The intergenerational transmission of education from parents to children is an important indicator of societal inclusiveness and educational inequality. The present study uses restricted-access data from the National Longitudinal Survey of Youth 1997 (NLSY97) to investigate whether intergenerational educational transmission varies by county-level demographic and socioeconomic characteristics for Hispanic Americans. Based on parental birthplace, Hispanic Americans are grouped into 3+ generation (i.e. children of native-born Hispanic parents) and 2nd generation (i.e. children of foreign-born Hispanic parents). Men and women are analyzed separately. The results indicate that intergenerational educational mobility is higher if 3+ generation Hispanic men reside in areas with a larger Hispanic population, and if 2nd generation Hispanic men reside in areas with a larger college-educated population, during their adolescent years. County-level socioeconomic characteristics do not seem to affect intergenerational educational mobility of Hispanic women, non-Hispanic white men, or non-Hispanic white women. Theoretical and empirical implications of the findings are discussed.